Assessment of Domestic Water Usage and Wastage in Urban Bangladesh : A Study of Rajshahi City Corporation: A Study of Rajshahi City Corporation - Imran Hossain; A.K.M. Mahmudul Haque; S.M. Akram Ullah (Pusbindiklatren Bappenas, 2023)
This study investigates domestic water consumption and waste patterns in Rajshahi City Corporation (RCC), Bangladesh, with an emphasis on identifying factors influencing water waste. Employing a mixed-methods approach involving surveys, monitoring, and interviews, the research evaluates both quantitative and qualitative data. The findings indicate significant positive correlations between water consumption, education level, water safety awareness, availability, and source proximity. Notably, a negative relationship between consumption and water source closeness is observed. Variations in consumption across residential zones, including households exceeding recommended water consumption, are highlighted. Water waste practices, such as taps left running and excessive usage, are identified. Additionally, inadequate access to clean drinking water is also revealed. The study offers insights into research-based strategies to conserve water, enhance sustainable management, and ensure efficient urban water resource utilization in Bangladesh.